2017
DOI: 10.3389/fpls.2017.02025
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Environmental Conditions and Genetic Background of Arabica Coffee (C. arabica L) on Leaf Rust (Hemileia vastatrix) Pathogenesis

Abstract: Global warming is a major threat to agriculture worldwide. Between 2008 and 2013, some coffee producing countries in South and Central America suffered from severe epidemics of coffee leaf rust (CLR), resulting in high economic losses with social implications for coffee growers. The climatic events not only favored the development of the pathogen but also affected the physiological status of the coffee plant. The main objectives of the study were to evaluate how the physiological status of the coffee plant mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
66
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(73 citation statements)
references
References 48 publications
3
66
0
4
Order By: Relevance
“…Among these performing hybrids genotypes (for yield and stability), Centroamericano-H1 and Mundo Maya-H16 are resistant to rust disease while Evaluna-H18 and Nayarita-H19 are weakly susceptible to rust. Many studies have shown that plant rust incidence is linked to productivity (Avelino et al 2006;Toniutti et al 2017Toniutti et al , 2019. In our study, the GSI index (which takes into account both productivity and productivity stability) is not related to the level of rust incidence.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…Among these performing hybrids genotypes (for yield and stability), Centroamericano-H1 and Mundo Maya-H16 are resistant to rust disease while Evaluna-H18 and Nayarita-H19 are weakly susceptible to rust. Many studies have shown that plant rust incidence is linked to productivity (Avelino et al 2006;Toniutti et al 2017Toniutti et al , 2019. In our study, the GSI index (which takes into account both productivity and productivity stability) is not related to the level of rust incidence.…”
Section: Discussionmentioning
confidence: 50%
“…In theory, this higher genetic potential also means it is more likely to be adaptable across a wide range of environments. In previous works we showed that Arabica F1 hybrids produced more than their parents (Bertrand et al 2005) and also eliminate many of the trade-offs of the past-for example, coffee leaf rust resistance versus quality (Toniutti et al 2017).…”
Section: Introductionmentioning
confidence: 95%
“…Globally suitable agro-climatic zones for growing Coffee arabica are expected to significantly diminish, although increased temperature could favour its production at higher elevation and close to the Equator (Ovalle-Rivera et al 2015). With higher temperatures increased potential damage by coffee berry borer Hypothenemus hampei (Jaramillo et al 2011) and coffee leaf rust Hemileia vastatrix disease (Toniutti et al 2017) are expected.…”
Section: Introductionmentioning
confidence: 99%
“…Manual thinning by coffee workers to reduce fruits by 50% (which in fact reduced yield 38%) resulted in between 4 to 6% of lower RI (respectively for the inbred and the hybrid). Similar results by (Toniutti 2017) confirmed that CLR sporulation depends on the physiological status of the coffee plant, which itself depends on agronomic conditions and on hybrid vigour. Here we focused on the transcriptome of the coffee leaf response from these agronomic management strategies to control coffee leaf rust disease (CLR).…”
Section: Discussionsupporting
confidence: 73%